PHYSICO-CHEMICAL CHARACTERISTICS AND HEAVY METAL CONCENTRATIONS OF ALETO STREAM, ELEME, RIVERS STATE, NIGERIA - Hamilton-Amachree, A.; Gbarakoro, S. L; Adooh, L. S. K. (International Journal of Research -GRANTHAALAYAH, 2022)
Aim: The physico-chemical properties and heavy metal concentrations of Aleto stream were investigated to determine its status. Research Design: Samples were collected randomly from four points; upstream, outfall, downstream of Aleto stream with Agbonchia stream serving as control. Methodology: The physico-chemical parameters: temperature, pH, EC, turbidity, TSS, TDS, total hardness, calcium hardness, alkalinity, nitrate, phosphate, chloride, COD, BOD, DO, color, odor and taste were determined using standard methods. Heavy metal levels were determined using AAS. Results: The physico-chemical characteristics revealed range values of EC (5400-5600 µs/cm), turbidity (39-90NTU), TDS (2780-3020 mg/L), Total Hardness (550-600 mg/L), calcium hardness (500-550 mg/L), chloride (1798-2043 mg/L), COD (50-115 mg/L), BOD (12-23 mg/L) and DO (12-15 mg/L) were above WHO permissible limits for upstream, outfall and downstream while alkalinity, nitrate, phosphate, and temperature ranges of 22-23 mg/L, 3.7-4.7 mg/L, 0.6 -1.9 mg/L and 26-26.3OC respectively were within maximum allowable limit of WHO. The pH was slightly alkaline for Aleto Stream. Color and taste for the water samples were above recommended limits. The heavy metal levels were Fe: 0.488, 0.499, 0.499 and 0.142; Zn: 0.094, 0.094, 0.095 and 0.061; Cd: 0.055, 0.053, 0.051 and 0.022; Pd: 0.358, 0.386, 0.419 and 0.110; Cr: 0.131, 0.141, 0.152 and 0.018; As: <0.01, <0.01. <0.01 and <0.01 for downstream, upstream, outfall and control samples respectively. The result suggests that there is significant difference in the mean values of the parameters in the water sources considered. Conclusion: Thus, regular surveillance should be carried out on the stream to detect any alteration in the water quality in order to avert any outbreak of health disorders.